Coordinated Ca2+ release from intracellular Ca2+ stores - Petersen, Ole (Henry Stewart Talks, 2007)
Calcium release from intracellular stores as opposed to Calcium entry from the external solution, The pioneers of Calcium signaling, Patch clamp recording combined with optical Calcium measurements, Calcium measurements in various organelles, Different Calcium releasing messengers, Calcium-mediated NO release, Calcium tunnels, Stimulusmetabolism coupling, Calcium release from the endoplasmic reticulum and from acid stores, Local and global Calcium signaling also in the intact tissue
Archived at 2021/02/25